Polymorphic ventricular tachycardia, ischaemic ventricular fibrillation, and torsade de pointes: importance of the QT and the coupling interval in the differential diagnosis. (10th March 2021) - Rosso, Raphael; Hochstadt, Aviram; Viskin, Dana; Chorin, Ehud; Schwartz, Arie Lorin; Tovia-Brodie, Oholi; Laish-Farkash, Avishag; Havakuk, Ofer; Gepstein, Lior; Banai, Shmuel; Viskin, Sami
Abstract: Aims: Distinctive types of polymorphic ventricular tachycardia (VT) respond differently to different forms of therapy. We therefore performed the present study to define the electrocardiographic characteristics of different forms of polymorphic VT. Methods and results: We studied 190 patients for whom the onset of 305 polymorphic VT events was available. The study group included 87 patients with coronary artery disease who had spontaneous polymorphic VT triggered by short-coupled extrasystoles in the absence of myocardial ischaemia. This group included 32 patients who had a long QT interval but nevertheless had their polymorphic VT triggered by ectopic beats with short coupling interval, a subcategory termed 'pseudo-torsade de pointes] (TdP). For comparison, we included 50 patients who had ventricular fibrillation (VF) during acute myocardial infarction ('ischaemic VF' group) and 53 patients with drug-induced TdP ('true TdP' group). The QT of patients with pseudo-TdP was (by definition) longer than that of patients with polymorphic VT and normal QT (QTc 491.4 ± 25.2 ms vs. 447.3 ± 55.6 ms, P  < 0.001). However, their QT was significantly shorter than that of patients with true TdP (QTc 564.6 ± 75.6 ms, P  < 0.001). Importantly, the coupling interval of the ectopic beat triggering the arrhythmia was just as short during pseudo-TdP as during polymorphic VT with normal QT (359.1 ± 38.1 ms vs. 356.6 ± 39.4 ms, P  = 0.467) but was much shorter than during true TdP (581.2 ± 95.3 ms, P  < 0.001). Conclusions: The coupling interval helps discriminate between polymorphic VT that occurs despite a long QT interval (pseudo-TdP) and polymorphic arrhythmias striking because of a long QT (true TdP). Graphical Abstract: